Effects of Bacillus velezensis Supplementation on the Growth Performance, Immune Responses, and Intestine Microbiota of Litopenaeus vannamei - Chen, Lizhu; Lv, Chengjie; Li, Bin; Zhang, Huawei; Ren, Lihua; Zhang, Qianqian; Zhang, Xiaoli; Gao, Jiqing; Sun, Chunxiao; Hu, Shunxin (Frontiers in Marine Science, 2021)
In the present study, Bacillus velezensis (BV007, CGMCC NO.20039) was isolated from the gut of Litopenaeus vannamei, and the effects of BV007 on the growth performance, immune responses and intestine microbiota of the shrimp were investigated. A total of 1200 healthy shrimp (3.0 ± 0.3 cm, 0.32 ± 0.8 g) were randomly divided into four groups, and fed diets supplemented with different levels of BV007 (C: 0; BV1: 1 × 105 CFU/g; BV2: 1 × 107 CFU/g; BV3: 1 × 109 CFU/g) for 8 weeks. The results showed a significantly increased final body length (FBL), length gain rate (LGR), final body weight (FBW), weight gain rate (WGR), plumpness index (PI), and specific growth rate (SGR) in shrimp fed BV007 for 42 days compared with shrimp fed with control diet. The activity of α-amylase in hepatopancreas was also significantly increased in the BV007-administered groups. After 42 days of growth trial, the challenge test with Vibrio parahaemolyticus was conducted for two weeks. Enhanced immune responses were exhibited by shrimp fed BV007 after V. parahaemolyticus challenge, particularly in respiratory bursts and superoxide dismutase, catalase, and alkaline phosphatase activities. Moreover, the administration of BV007 could considerably increase the abundance of potential probiotics (Bacillus) and reduced the abundances of potential pathogenic bacteria (Vibrio) in shrimp intestines. In conclusion, dietary supplementation with B. velezensis BV007 could promote the growth performance, enhance the immune responses, and modulate the intestine microbiota of shrimp, and 107 CFU/g feed was recommended to be used as a feed additive to enhance the growth and health status of shrimp.